Pengaruh Mekanisme Kepemilikan Manajerial, Kecakapan Manajerial, Tingkat Pengungkapan Laporan Keuangan Terhadap Manajemen Laba Dengan Kualitas Audit Sebagai Variabel Intervening. - Puspita, Erna; Kusumaningtyas, Dian (Universitas Nusantara PGRI Kediri, 2017)
The purpose of this study is to empirically analyze the influence of managerial ownership mechanisms, managerial skills, and the level of disclosure of financial statements to profit management with audit quality as intervening variables. The population in this research is all manufacturing companies, sample selection using purposive sampling with a total of 46 companies. Techniques and approaches used are quantitative descriptive, ie by describing the relationship of each variable through intervening variables. Data analysis techniques use path analysis.The results of the data analysis obtained Managerial ownership, managerial skills, financial disclosure level influenced both directly and indirectly through variable intervening quality audit to earnings management at manufacturing company registered in IDX period 2014-2016. Keywords: